The Influence Of Competency, Training, And Organizational Culture On The Performance of BRI Employees In The Situbondo Branch With Job Satisfaction As Intervening Variable - Eko Yuliarso, Ferry; Ariyantiningsih, Febri; Yahya Arief, Mohammad (International Journal of Economics, Business and Innovation Research, 2026)
The purpose of this study is to analyze the influence of the variables of Training Competence and Organizational Culture on the Performance of BRI Employees at the Situbondo Branch with Job Satisfaction as an Intervening Variable. By using the Partial Least Square (PLS) Structural equation model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application Competence has a positive but not significant effect on Job Satisfaction, Training has a positive but not significant effect on Job Satisfaction, Organizational Culture has a significant positive effect on Job Satisfaction, Competence has a significant positive effect on Performance, Training has a positive but not significant effect on Performance, Organizational Culture has a significant positive effect on Performance, Job Satisfaction has a positive but not significant effect on Performance, Competence has a positive but not significant effect on Performance through Job Satisfaction, Training has a positive but not significant effect on Performance through Job Satisfaction, Organizational Culture has a positive but not significant effect on Performance through Job Satisfaction.